Subcutaneous and Intraosseous Fat Necrosis Associated with Chronic Pancreatitis - Jelena D. Zivadinovic; Marko M. Stojanovic; Marija D. Stosic; Aleksandar R. Zivadinovic; Radmilo Jankovic; Marko D. Gmijovic; Ilija Golubovic; Biljana Stosic; Nebojsa S. Ignjatovic; Miroslav P. Stojanovic (Medicina, 2022)
Background: Extra-abdominal manifestations of fat necrosis, like subcutaneous fat necrosis, polyarthritis, and polyserositis may appear with an occurrence rate of about 0.8%, wherein intraosseous fat necrosis is a more rare complication of pancreatitis, with few reports in English literature. Case report: A 34-year-old male with a 15-year-history of alcohol abuse was hospitalized several times in the last few years because of attacks of relapsed chronic pancreatitis. After the last attack, pancreatitis came in a stable state (“burned out”) with no symptoms and signs of the disease. The patient had been free of symptoms for 28 months since the last admission when he came with sub-febrile temperature, huge pain, swelling, and erythema in the area of the left lateral malleolar region with propagation in the foot. Blood biochemistry was normal. Conventional radiography showed multiple sites of osteolysis in the left calcaneus. Images on multislice computed tomography (MSCT) with 3D reconstruction revealed hypodense focuses that corresponded to osteonecrosis areas and bone marrow edema in the left calcaneus. Conclusions: The possibility of intraosseous fat necrosis should be considered in situations of unexplained polyarthritis or panniculitis, particularly in individuals with alcohol abuse or pancreatic disease.